Higher neutrophil counts before thrombolysis for cerebral ischemia predict worse outcomes - Maestrini, Ilaria (Neurology, 2015)
OBJECTIVE: To determine whether higher neutrophil counts before IV recombinant tissue plasminogen activator (rtPA) administration in ischemic stroke (IS) patients are associated with symptomatic intracerebral hemorrhages (sICH) and worse outcomes at 3 months. METHODS: Blood samples for leukocyte, neutrophil, and lymphocyte counts were drawn before IV rtPA administration in IS patients included in the cohorts of Lille and Helsinki. The primary endpoint was sICH (European Cooperative Acute Stroke–II definition). Secondary endpoints were death and excellent (modified Rankin Scale [mRS] score 0–1 or equal to prestroke mRS) and good (mRS score 0–2 or equal to prestroke mRS) outcomes at 3 months. RESULTS: We included 846 patients (median age 71 years; 50.8% men). The neutrophil count and neutrophil to lymphocyte ratio (NLR) were independently associated with the 4 endpoints: sICH (adjusted odds ratio [(adj)OR] for an increase of 1,000 neutrophils = 1.21 and (adj)OR 1.11, respectively), death ((adj)OR 1.16 and (adj)OR 1.08), and excellent ((adj)OR 0.87 and (adj)OR 0.85) and good ((adj)OR 0.86 and (adj)OR 0.91) outcomes. The total leukocyte count was not associated with any of the 4 endpoints. The best discriminating factor for sICH was NLR ≥4.80 (sensitivity 66.7%, specificity 71.3%, likelihood ratio 2.32). Patients with NLR ≥4.80 had a 3.71-fold increased risk for sICH (95% confidence interval (adj)OR: 1.97–6.98) compared to patients with NLR <4.80. CONCLUSIONS: Higher neutrophil counts and NLR are independently associated with sICH and worse outcome at 3 months. The identification of mediators of this effect could provide new targets for neuroprotection in patients treated by rtPA.